Carbon nanotubes and dispersion containing same

Carbon nanotubes with specific surface area, bulk density, and powder resistance properties address the issue of low solubility and dispersibility, achieving improved dispersibility and electrical conductivity for use in lithium secondary batteries.

JP2025511485AActive Publication Date: 2025-04-16LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024552276
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-10-28
Filing Date
2023-10-26
Publication Date
2025-04-16
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

Carbon nanotubes have low solubility and dispersibility due to strong van der Waals attraction, leading to aggregation and increased viscosity in dispersions, which hinders their effective use as conductive materials in lithium secondary batteries.

Method used

Development of carbon nanotubes with specific physical properties, including a specific surface area of 320m²/g or greater, bulk density between 15 kg/m³ and 30 kg/m³, and powder resistance of 0.0080 Ω·cm to 0.0125 Ω·cm, which improves their dispersibility and electrical conductivity.

Benefits of technology

The carbon nanotubes with these specific properties maintain excellent viscosity and conductivity properties during dispersion production, allowing for stable and efficient use as conductive materials in lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511485000001
    Figure 2025511485000001
  • Figure 2025511485000002
    Figure 2025511485000002
  • Figure 2025511485000003
    Figure 2025511485000003
Patent Text Reader

Abstract

The present invention relates to carbon nanotubes that satisfy a specific formula. The carbon nanotubes of the present invention are particularly suitable for use as conductive materials in secondary batteries because they simultaneously exhibit excellent dispersibility and electrical conductivity when applied to a dispersion liquid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0141851, filed on October 28, 2022, and all contents disclosed in the documents of said Korean patent application are incorporated by reference into this specification. The present invention relates to carbon nanotubes that have a low viscosity and a low powder resistance when produced as a dispersion, and to a dispersion containing the carbon nanotubes. [Background technology]

[0002] Carbon nanomaterials include fullerenes, carbon nanotubes (CNTs), graphene, graphite nanoplates, etc., depending on the shape of the material. Among them, carbon nanotubes are giant molecules in which a hexagonal honeycomb-shaped graphite sheet, in which one carbon atom is bonded to three other carbon atoms, is rolled up into a nano-sized diameter.

[0003] Carbon nanotubes are hollow, so they are light, have electrical conductivity as good as copper, thermal conductivity as good as diamond, and tensile strength comparable to steel. Depending on their curled shape, they are divided into single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), and rope carbon nanotubes.

[0004] In recent years, the field in which the most active research has been conducted on the use of carbon nanotubes is the field of lithium secondary batteries. The ultimate goal of lithium secondary batteries is to store more electrical energy in a smaller size, and as one of the methods for improving the electrode density of lithium secondary batteries and manufacturing electrodes with higher energy density per unit volume, a method of using carbon nanotubes as a conductive material has been researched. In general, high-density electrodes are formed by molding electrode active material particles having a size of several μm to several tens of μm using a high-pressure press, so that the particles are deformed during the molding process, the spaces between the particles are reduced, and the permeability of the electrolyte is likely to decrease. In order to solve this problem, a material having excellent electrical conductivity and strength is used as a conductive material when manufacturing electrodes, and carbon nanotubes are also widely used as a conductive material because of their excellent strength and electrical conductivity. When a conductive material is used when manufacturing electrodes, the conductive material is dispersed between the compressed electrode active material, maintaining fine pores between the active material particles, making it easy for the electrolyte to penetrate, and the excellent conductivity can reduce the resistance inside the electrode.

[0005] However, the biggest problem in using carbon nanotubes as a conductive material is the low solubility and dispersibility of the carbon nanotubes themselves. Carbon nanotubes have a problem in that they cannot be stably dispersed in an aqueous solution due to the strong van der Waals attractive forces between them, and aggregation occurs. If carbon nanotubes aggregate in a dispersion, the processability of the dispersion decreases and the dispersion cannot be applied uniformly, so it is preferable to apply the dispersion with the viscosity of the dispersion reduced to the minimum.

[0006] Various methods are known as a method for improving the decrease in dispersibility of carbon nanotube dispersion liquid. As an example, a method has been proposed in which carbon nanotubes are dispersed in a dispersion medium by a mechanical dispersion treatment such as ultrasonic treatment. However, in this method, although the dispersibility is excellent while the ultrasonic treatment is being applied, the carbon nanotubes immediately begin to aggregate when the ultrasonic treatment is terminated, and the carbon nanotubes immediately aggregate even when the carbon nanotube concentration is higher than a certain level. In addition, a method has been proposed for stabilizing the dispersion of carbon nanotubes using various dispersants, but these methods also have the problem that it is difficult to suppress the increase in viscosity that may occur when carbon nanotubes are dispersed in a dispersion medium at a high concentration.

[0007] Therefore, rather than using mechanical dispersion treatments such as ultrasonic treatment or auxiliary means such as the use of dispersants, it is necessary to produce novel carbon nanotubes that can further improve dispersibility by improving the physical properties of the carbon nanotubes themselves. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2017-0031061 (March 20, 2017) Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide novel carbon nanotubes that are particularly suitable for use as a conductive material because they have a low viscosity when produced as a dispersion and a low powder resistance when produced as a slurry, and a dispersion containing the carbon nanotubes. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides novel carbon nanotubes, a dispersion containing the carbon nanotubes, and a positive electrode slurry composition containing the dispersion.

[0011] (1) Specifically, the present invention provides a carbon nanotube that satisfies the following formula 1:

[0012] [Formula 1] -0.004*A+0.0385≦R≦-0.004*A+0.0425

[0013] In the above formula 1, R is the powder resistivity of the carbon nanotube (Ω·cm); A is ln{(purity of carbon nanotubes (wt%)*specific surface area (m 2 / g) / bulk density (kg / m 3 )}, The specific surface area of ​​the carbon nanotube is 320 m 2 / g or more, The bulk density of the carbon nanotubes is 30 kg / m 3 The following is the result.

[0014] (2) In the present invention, the specific surface area of ​​the carbon nanotube is 320 m 2 / g~500m 2 The carbon nanotube according to the above (1) is provided, wherein the average molecular weight of the carbon nanotube is 1 / g.

[0015] (3) In the present invention, the bulk density of the carbon nanotubes is 15 kg / m 3 ~30kg / m 3 The present invention provides a carbon nanotube according to the above (1) or (2),

[0016] (4) The present invention provides the carbon nanotube according to any one of (1) to (3) above, wherein R is 0.0125 Ω·cm or less.

[0017] (5) The present invention provides the carbon nanotube according to any one of (1) to (4) above, wherein R is 0.0080 Ω·cm to 0.0125 Ω·cm.

[0018] (6) The present invention provides a carbon nanotube dispersion liquid, comprising the carbon nanotubes according to any one of (1) to (5) above and a dispersion medium.

[0019] (7) In the present invention, there is provided the carbon nanotube dispersion liquid according to (6) above, wherein the dispersion medium is one or more selected from the group consisting of N-methylpyrrolidone, pyridine, dimethylaminobenzene, and diethylaminobenzene.

[0020] (8) In the present invention, there is provided the carbon nanotube dispersion according to (6) or (7) above, wherein the carbon nanotube content in the dispersion is 0.05% by weight to 5% by weight.

[0021] (9) The present invention provides a positive electrode slurry composition, comprising the carbon nanotube dispersion liquid according to any one of (6) to (8) above, a positive electrode material, and a stabilizer.

[0022] (10) In the present invention, there is provided the positive electrode slurry composition according to (9) above, in which the stabilizer is contained in an amount of 10% by weight to 100% by weight based on the content of the carbon nanotubes in the positive electrode slurry composition. Effect of the Invention

[0023] The carbon nanotubes of the present invention have a low viscosity during production of the dispersion, so that the carbon nanotube content in the dispersion state can be made to be above a certain level, and the powder resistance of the slurry is also low, making them particularly suitable for use as a conductive material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will now be described in more detail. The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0025] The term "carbon nanotube" as used in the present invention refers to a secondary structure formed by the assembly of carbon nanotube units into a bundle shape in whole or in part, and the carbon nanotube units have graphite sheets in the shape of cylinders with nano-sized diameters and sp2 bond structure. In this case, the graphite sheets can exhibit conductive or semiconductive properties depending on the angle and structure of the curved graphite sheets. Carbon nanotube units can be classified into single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs), and multi-walled carbon nanotubes (MWCNTs) depending on the number of bonds that make up the walls, and the thinner the wall thickness, the lower the resistance. The carbon nanotubes of the present invention may include any one or more of single-walled, double-walled, and multi-walled carbon nanotube units.

[0026] Carbon Nanotubes The present invention provides a carbon nanotube characterized by satisfying the following formula 1.

[0027] [Formula 1] -0.004*A+0.0385≦R≦-0.004*A+0.0425

[0028] In the above formula 1, R is the powder resistivity of the carbon nanotube (Ω·cm); A is ln{(purity of carbon nanotubes (wt%)*specific surface area (m 2 / g) / bulk density (kg / m 3 )}, The specific surface area of ​​the carbon nanotube is 320 m 2 / g or more, The bulk density of the carbon nanotubes is 30 kg / m 3 The following is the result.

[0029] The inventors of the present invention have studied the physical properties of carbon nanotubes that enable both viscosity characteristics and electrical conductivity characteristics to be maintained at excellent levels during the preparation of a dispersion, and have found that the powder resistivity, purity, specific surface area, and bulk density of carbon nanotubes satisfy the above formula 1, and the specific surface area of ​​the carbon nanotubes is 320 m 2 / g or more and a bulk density of 30 kg / m 3 It was confirmed that, when the temperature is as follows, both the dispersibility and electrical conductivity of the carbon nanotubes can be well maintained, and the present invention was completed based on this.

[0030] More specifically, when the production conditions of the catalyst used for producing carbon nanotubes, specifically the content of the active component, the ratio of the main catalyst component to the cocatalyst component, the content of the organic acid in the precursor solution, the calcination temperature, etc., are changed, the physical properties of the carbon nanotubes produced from the catalyst also change. Therefore, by changing the production conditions of the catalyst, various carbon nanotubes having different physical properties can be synthesized. Furthermore, as a result of confirming the correlation between the dispersibility, electrical conductivity, and physical properties of various synthesized carbon nanotubes by various methods, it was found that carbon nanotubes satisfying the above formula 1 have the characteristic of being excellent in both dispersibility and electrical conductivity.

[0031] More specifically, the formula 1 indicates that there is a correlation between the powder resistivity of carbon nanotubes and the purity, specific surface area, and bulk density. The formula 1 is derived based on various data, and it can be confirmed that carbon nanotubes that satisfy the formula 1 have excellent dispersibility and electrical conductivity at the same time.

[0032] The A value and the R value in the formula 1 have different units, but in the present invention, the units of each value are ignored and each value is assumed to be a dimensionless number. However, since each value may differ depending on the units of the powder resistivity, purity, specific surface area, and bulk density of the carbon nanotubes, which are variables of each value, when applying the formula 1, the units of each variable are fixed as follows.

[0033] Carbon nanotube powder resistivity (R) unit: Ω cm Carbon nanotube purity unit: weight percent The specific surface area of ​​carbon nanotubes is measured in m 2 / g Bulk density of carbon nanotubes in kg / m 3

[0034] On the other hand, in the carbon nanotubes provided by the present invention, the specific surface area of ​​the carbon nanotubes is 320 m 2 / g or more, preferably 320m 2 / g~500m 2 / g. If carbon nanotubes are defined only by the formula 1 without any range restriction on the specific surface area of ​​the carbon nanotubes, virtually an infinite number of carbon nanotubes can satisfy the formula 1, and the range may include not only carbon nanotubes having excellent dispersibility and electrical conductivity as the object of the present invention, but also carbon nanotubes not having excellent dispersibility and / or electrical conductivity. Therefore, the carbon nanotubes of the present invention must satisfy the formula 1 and have a specific surface area within the above-mentioned range. Meanwhile, the specific surface area may be measured by the BET method, and more specifically, may be calculated by determining the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by BEL Japan.

[0035] Furthermore, the carbon nanotube of the present invention has a bulk density of 30 kg / m 3 Less than 15 kg / m 3 ~30kg / m 3When the above formula 1 and the specific surface area conditions are satisfied and the bulk density of the carbon nanotubes is within the above range, the carbon nanotubes have particularly excellent dispersibility and electrical conductivity, and sufficient electrical conductivity can be provided even with a low carbon nanotube content during preparation of the dispersion. Meanwhile, the bulk density can be calculated by measuring the weight of the carbon nanotubes that have fallen into a container by free fall using a 25 ml SUS measuring cup and dividing the measured weight by the volume of the container.

[0036] The powder resistance R of the carbon nanotubes of the present invention may be 0.0125 Ω·cm or less, and more preferably 0.0080 Ω·cm to 0.0125 Ω·cm. As in the case of the bulk density, when the powder resistance of the carbon nanotubes satisfies the formula 1 and the specific surface area condition and is within the range, the carbon nanotubes can have particularly excellent electrical conductivity. Meanwhile, the powder resistance may be measured by measuring the resistance due to pressure at a compressed density of 1 g / cc using MCP-PD51 equipment manufactured by Nittoseiko Analytech.

[0037] The carbon nanotubes of the present invention may have a purity of 80% by weight or more, and more preferably 83% by weight or more. The purity means the content of the carbon nanotubes remaining after impurities in the carbon nanotubes are removed, and can be calculated by the following formula. Purity = (carbon nanotube yield - catalyst input) / carbon nanotube yield * 100%

[0038] Carbon nanotube dispersion The present invention provides a dispersion liquid containing the above-mentioned carbon nanotubes. More specifically, the present invention provides a carbon nanotube dispersion liquid containing the above-mentioned carbon nanotubes and a dispersion medium.

[0039] In the carbon nanotube dispersion of the present invention, the dispersion medium may be one or more selected from the group consisting of N-methylpyrrolidone, pyridine, dimethylaminobenzene, and diethylaminobenzene, and may be preferably N-methylpyrrolidone. When one of the above-listed dispersion media is used as the dispersion medium, the carbon nanotubes can be smoothly dispersed, and then, only the dispersion medium can be selectively and easily removed during the coating and baking process of the dispersion.

[0040] In the carbon nanotube dispersion of the present invention, the carbon nanotube content in the dispersion may be 0.05% by weight to 5% by weight, and preferably 0.5% by weight to 3% by weight. If the carbon nanotube content in the dispersion is lower than the above range, sufficient electrical conductivity cannot be achieved, and if the carbon nanotube content is higher than the above range, the excessive carbon nanotubes may aggregate, increasing the viscosity, which may significantly reduce the processability of the dispersion itself.

[0041] In the carbon nanotube dispersion of the present invention, the dispersion may contain polysaccharides and monosaccharides such as carboxylmethylcellulose (CMC), hydroxyethylcellulose, pectin, alginic acid, guar gum, locust bean gum, gum arabic, dextrin, altose, sorbitol, lactose, rice starch, and sucrose; sodium cholate, gelatin, and polyvinyl alcohol; anionic surfactants such as naphthalenesulfonic acid-formaldehyde condensates and alkylbenzenesulfonates, cationic surfactants, nonionic surfactants, polyether-modified silicone surfactants, and hydrogenated nitrile butadiene rubber (HNBR) as dispersants. Particularly preferably, the dispersant may be HNBR. The dispersant may be contained in an amount of 0.1% by weight to 5% by weight, preferably 0.3% by weight to 3% by weight, based on the total weight of the dispersion. When the content is within the above range, the viscosity of the dispersion may be low and the viscosity stability may be excellent.

[0042] Positive electrode slurry composition Since the carbon nanotube dispersion provided by the present invention has excellent electrical conductivity, it can be used as a conductive material for the positive electrode slurry composition. Accordingly, the present invention provides a positive electrode slurry composition containing the above-described dispersion.

[0043] Specifically, the present invention provides a positive electrode slurry composition containing the above-described carbon nanotube dispersion, a positive electrode material, and a stabilizer. The dispersion is as described above.

[0044] The positive electrode material is not particularly limited as long as it can be used as a positive electrode material for a lithium secondary battery. For example, known positive electrode materials such as LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(Ni a Co b Mn c )O2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-Y Co Y O2, LiCo 1-Y Mn Y O2, LiNi 1-Y Mn Y O2 (where 0 < Y < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-Z Ni Z O4, LiMn 2-Z Co Z O4 (where 0 < Z < 2) may be used as the positive electrode material, either any one selected from the group consisting of these or a mixture of two or more thereof.

[0045] In the carbon nanotube positive electrode slurry composition of the present invention, the stabilizer may be polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), or a mixture thereof. The stabilizer may be included in an amount of 10 wt% to 100 wt% based on the carbon nanotube content in the positive electrode slurry composition, and preferably in an amount of 30 wt% to 70 wt%. When the amount is within the above range, the stability during the preparation of the slurry may be more excellent.

[0046] Hereinafter, the present invention will be described in more detail with reference to examples and experimental examples in order to specifically explain the present invention, but the present invention is not limited to these examples and experimental examples. The examples of the present invention may be modified in various different forms, and the scope of the present invention should not be interpreted as being limited to the examples described below. The examples of the present invention are provided to more specifically explain the present invention to those having average knowledge in the art.

[0047] Catalyst manufacturing example Co(NO3)2·6H2O was used as the cobalt precursor, and NH4VO3 was used as the vanadium precursor. The cobalt precursor and vanadium precursor were dissolved in water, and anhydrous citric acid (CA) was also dissolved as a complexing agent to prepare a catalyst precursor composition. The catalyst precursor composition was thoroughly stirred and then added to the hydrotalcite carrier. The catalyst was then dried at 190°C for 5 hours in an oven, and then calcined at a specific calcination temperature in the atmosphere for 4 hours to complete the catalyst. In the above process, the amount of vanadium added was set to a molar ratio of 0.3 per mole of cobalt, and the anhydrous citric acid was set to a molar ratio of 0.13 per mole of cobalt. In the above process, various catalysts were prepared by changing the content of cobalt in the catalyst precursor composition, the ratio of cobalt to vanadium, the ratio of anhydrous citric acid to vanadium, the calcination temperature, etc., and the catalyst preparation conditions for each preparation example are summarized in Table 1 below.

[0048] [Table 1]

[0049] Examples and Comparative Examples Carbon nanotubes were synthesized using the catalyst used in the catalyst preparation example. Specifically, 0.3 g of the prepared catalyst was packed into a fixed-bed reactor, and nitrogen gas was injected into the fixed-bed reactor at 1600 sccm, and the internal temperature of the reactor was heated to the reaction temperature. Then, ethylene gas was injected as a carbon source gas at 400 sccm, and the reaction was continued for 90 minutes to synthesize carbon nanotubes. The catalysts and reaction temperature conditions used in each example and comparative example are summarized in Table 2 below.

[0050] [Table 2]

[0051] Experimental Example 1. Check whether the produced carbon nanotubes satisfy formula 1 The purity, specific surface area, bulk density, and powder resistivity of the carbon nanotubes produced in the examples and comparative examples were measured to confirm whether they satisfied Equation 1. Each physical property was measured by the following method.

[0052] 1) Purity: (carbon nanotube yield - catalyst input) / carbon nanotube yield * 100% 2) Specific surface area: The amount of nitrogen gas adsorbed at liquid nitrogen temperature (77K) was calculated using a BELSORP-mini II made by BEL Japan.

[0053] 3) Bulk density: Using a 25 ml SUS measuring cup, the weight of the carbon nanotubes that had fallen into the container by free fall was measured, and the measured weight was divided by the volume of the container to calculate the bulk density.

[0054] 4) Powder resistance: The resistance due to pressure at a compressed density of 1 g / cc was measured using MCP-PD51 equipment manufactured by Nittoseiko Analytech. The measured results are summarized in Table 3 below.

[0055] [Table 3]

[0056] As can be seen from Table 3 above, the carbon nanotubes of the examples of the present invention satisfy formula 1. On the other hand, the carbon nanotubes of Comparative Examples 1-1, 1-2, and 2-1 satisfy formula 1 but do not satisfy the specific surface area range required by the present invention, the carbon nanotube of Comparative Example 3-1 satisfies formula 1 but does not satisfy the bulk density range required by the present invention, and the carbon nanotube of Comparative Example 3-2 does not satisfy formula 1.

[0057] Experimental Example 2. Measurement of viscosity of carbon nanotube dispersion and powder resistance of slurry A dispersion was prepared using the carbon nanotubes prepared in the above examples and comparative examples. 1.0 g of the prepared carbon nanotubes and 0.6 g of a dispersant HNBR were added to 98.4 g of a dispersion medium N-methylpyrrolidone. Then, a dispersion was prepared using a high-pressure homogenizer under conditions of 1500 bar and 3 passes. The prepared dispersion was mixed with a cathode material so that the carbon nanotube content was 0.5 wt %, and PVDF was further added as a stabilizer so that the content was 60 wt % based on the carbon nanotube content to prepare a slurry. The slurry was dried in an oven at 130° C. to remove the dispersion medium, and a powder was obtained, and the powder resistance was measured.

[0058] The viscosity of the prepared dispersion and the powder resistance of the slurry were measured by the following methods. 1) Viscosity: The viscosity of the dispersion was measured at room temperature using a Brookfield DV2T instrument.

[0059] 2) Powder resistance of the slurry: The powder resistance due to pressure was measured at a compressed density of 2.5 g / cc using MCP-PD51 equipment manufactured by Nittoseiko Analytech Co., Ltd. The measurement results are summarized in Table 4 below.

[0060] [Table 4]

[0061] As can be seen from Table 4 above, when dispersions and slurries are produced using the carbon nanotubes of the embodiments of the present invention, the viscosity of the dispersion is maintained at an appropriate level, the processability is excellent, and the powder resistance of the slurry is low, enabling it to exhibit excellent performance when used as a conductive material.

[0062] On the other hand, in the case of the carbon nanotubes of the comparative examples which do not satisfy Formula 1 of the present invention or which do not satisfy the appropriate range of specific surface area or bulk density, the powder resistance during slurry production is much higher than that of the examples, and from this it can be confirmed that the carbon nanotubes are not suitable for use as conductive materials.

Claims

1. A carbon nanotube characterized by satisfying the following formula 1: [Formula 1] -0.004*A+0.0385≦R≦-0.004*A+0.0425 In the above formula 1, R is the powder resistivity of the carbon nanotube (Ω cm), A is ln{(purity of carbon nanotubes (wt%) x specific surface area (m 2 / g) / Bulk density (kg / m 3 )}, The specific surface area of ​​the carbon nanotube is 320 m 2 / g or more, The bulk density of the carbon nanotubes is 30 kg / m 3 The following is the result.

2. The specific surface area of ​​the carbon nanotube is 320 m 2 / g to 500m 2 The carbon nanotube according to claim 1, wherein the molecular weight is 1 / g.

3. The bulk density of the carbon nanotubes is 15 kg / m 3 ~30kg / m 3 2. The carbon nanotube according to claim 1,

4. 2. The carbon nanotube according to claim 1, wherein said R is 0.0125 Ω·cm or less.

5. 5. The carbon nanotube according to claim 4, wherein R is 0.0080 Ω·cm to 0.0125 Ω·cm.

6. The carbon nanotube according to any one of claims 1 to 5, and A carbon nanotube dispersion including a dispersion medium.

7. 7. The carbon nanotube dispersion liquid according to claim 6, wherein the dispersion medium is one or more selected from the group consisting of N-methylpyrrolidone, pyridine, dimethylaminobenzene, and diethylaminobenzene.

8. 7. The carbon nanotube dispersion according to claim 6, wherein the carbon nanotube content in the dispersion is 0.05% by weight to 5% by weight.

9. The carbon nanotube dispersion liquid according to claim 6 . Cathode materials, and A positive electrode slurry composition comprising a stabilizer.

10. The positive electrode slurry composition of claim 9, wherein the stabilizer is included in an amount of 10 to 100 wt % based on a content of the carbon nanotubes in the positive electrode slurry composition.

Citation Information

Patent Citations

  • Carbon nanotube with high specific surface area and method for producing the same

    JP2016501813A

  • Conductive material dispersion and lithium secondary battery manufactured using the same

    JP2018534747A

  • Carbon nanotube, carbon nanotube dispersion and their uses

    JP2021095314A

  • Process for preparing aggregates of carbon nanotubes

    KR1020160036910A

  • Driving method of robot

    KR1020210017452A